Chopsticks a cultural and culinary history - Wang, Q. Edward 1958- (Cambridge University Press, 2015)
Chopsticks have become a quintessential part of the Japanese, Chinese and Korean culinary experience across the globe, with more than one fifth of the world's population using them daily to eat. In this vibrant, highly original account of the history of chopsticks, Q. Edward Wang charts their evolution from a simple eating implement in ancient times to their status as a much more complex, cultural symbol today. Opening in the Neolithic Age, at the first recorded use of chopsticks, the book surveys their practice through Chinese history, before exploring their transmission in the fifth century to other parts of Asia, including Vietnam, Korea, Japan and Mongolia. Calling upon a striking selection of artwork, the author illustrates how chopstick use has influenced Asian cuisine, and how, in turn the cuisine continues to influence chopstick use, both in Asia and across the globe